Poverty in the Ucayali region: a social injustice 2004-2009 - Diaz Encinas, Alida Isidora (2011)
'Ihe airn ()t rhis srudy is TO analyze rhe evolurion of poveny in the Ucayali regio» in a pcnod of nve years, chrough the interprctation of sraiisncal data compilcd by IN El. and review of Regional Developmenr Plan Concerrcd 2007-2010 and orhcr documenrs relared to rhc copie. The results show dccrcasing rrends, but with markcd di fferences berwecn provinccs ami districrs as a result uf poor disrriburion C)t funcrions and not cquirable income distribution nnd lack of statc rcsources in rernote locations